2014
DOI: 10.1371/journal.pone.0084640
|View full text |Cite
|
Sign up to set email alerts
|

Smoking during Pregnancy: Findings from the 2009–2010 Canadian Community Health Survey

Abstract: ObjectivesSmoking during pregnancy may cause many health problems for pregnant women and their newborns. However, there is a paucity of research that has examined the predictors of smoking during pregnancy in Canada. This study used data from the 2009–2010 Canadian Community Health Survey (CCHS) to estimate the prevalence of smoking during pregnancy and examine the demographic, socioeconomic, health-related and behavioral determinants of this behavior.Methods and FindingsThe data were obtained from the 2009–20… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
47
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 62 publications
(59 citation statements)
references
References 25 publications
8
47
0
4
Order By: Relevance
“…Most items used in the survey were drawn from existing populationbased adolescent health surveys, such as the British Columbia Adolescent Health Survey (see Saewyc, Konishi, Rose & Homma, 2014) or health surveys participated in by young adults, such as the Canadian Community Health Survey (Cui, Shooshtari, Forget, Clara, & Cheung, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…Most items used in the survey were drawn from existing populationbased adolescent health surveys, such as the British Columbia Adolescent Health Survey (see Saewyc, Konishi, Rose & Homma, 2014) or health surveys participated in by young adults, such as the Canadian Community Health Survey (Cui, Shooshtari, Forget, Clara, & Cheung, 2014).…”
Section: Methodsmentioning
confidence: 99%
“…[63,64] Interestingly, even in recent years of advanced healthcare advice, there is evidence that women even in developed countries do not adhere strictly to recommendations around the time of conception that will ensure optimal fetal health and by extension reduce the risk of adult NCCDs later in life ( Table 4). [149][150][151][152][153][154][155][156][157][158][159] The World Health Organization recommends supplementation with several nutrients including folic acid, iron, and others during the time of conception and gestation (Table 5), [160][161][162][163][164] which many women may fail to take, creating an intrauterine environment that is similar to that of undernutrition in some respects. Moreover, some women may indulge in unhealthy lifestyles including smoking [165] despite evidence of its adverse effects on fetal health and long term consequences on adult NCCDs.…”
Section: Hypomethylation Of the Pancreatic Il13ra2 Genementioning
confidence: 99%
“…11 states of the USA Smoking During pregnancy [157] Among 369 547 pregnant women in Canada, 23% were smokers in 2009-2010, with higher prevalence in the Northern territories (59.3%) Canada Perinatal alcohol consumption [158] Among 1594 pregnant women, 84% had consumed alcohol the year prior to pregnancy (14% considered hazardous consumption) and 6% at least once during pregnancy Sweden Perinatal alcohol consumption [159] Among 1303 pregnant women, two-thirds and half in the first trimester consumed alcohol over the Department of Health (UK) guidelines of ≤2 units per week before pregnancy Leeds, UK a)…”
Section: Australiamentioning
confidence: 99%
“…Despite increased awareness of its detrimental effects, w10-23% of pregnant women continue to smoke worldwide, with rates higher than 50% in some communities (i.e., Northern Territories in Canada) (Tong et al 2013, Cui et al 2014. Among women who attempt to quit smoking during pregnancy, it is reported that only half will successfully abstain; the steep rates of relapse are partly attributable to the highly addictive nature of nicotine in cigarettes (Tong et al 2013, Orton et al 2014.…”
Section: Introductionmentioning
confidence: 99%